Analisis Pengelolaan Arsip Inaktif pada Direktorat X, Kementerian XYZ - Ditri Zulfikar; Roni Faslah; Muhammad Ikhwan (Jurnal Ekonomi dan Bisnis Digital, 2026)
Inactive records management constitutes an important part of the records life cycle, playing a significant role in ensuring information availability, organizational accountability, and orderly administrative processes within government institutions. This study aims to analyze the process of inactive records management, assess its compliance with applicable archival regulations, and identify the challenges encountered in the Processing Unit of the Directorate for Field Mobilization Development, Ministry of Population and Family Development. This research employs a descriptive qualitative approach. Data were collected through participatory observation, in-depth interviews with three informants, and documentation studies. Data analysis used the Miles and Huberman model covering data reduction, data display, and conclusion drawing. The results indicate that inactive records management has been implemented through several stages: records identification based on classification and the Records Retention Schedule (RRS), records sorting, preparation of records lists, physical arrangement in archival boxes, and transfer of records to the Records Unit. However, implementation has not been fully in accordance with Law Number 43 of 2009, ANRI Regulation Number 9 of 2018, and BKKBN Head Regulation Number 20 of 2020. Discrepancies are observed in physical maintenance, storage conditions, and suboptimal archival facilities. Main challenges include limited human resources, uneven understanding of archival principles, inadequate storage facilities, and insufficient technical guidance.